Peramalan Nilai Ekspor di Indonesia Dengan Hierarchical Time Series Menggunakan Fungsi Transfer - Deo Saputra (Bandung Conference Series: Statistics, 2024)
Abstract. Hierarchical forecasting is a breakdown of forecasting that allows joint forecasting at all levels of the hierarchy. There are two approaches used, namely the top-down and bottom-up approaches. This research uses a bottom-up approach, top-down historical proportions, and top-down forecasting proportions. Hierarchical forecasting can be applied to several time series models. The transfer function model is used in this research. This research aims to model the export value in Indonesia with a transfer function and export value based on export sector disaggregation. The data is divided into two levels, namely level 0 for data on export values for all sectors in Indonesia, and level 1 for data on export values per sector (oil and non-oil and gas). Based on the sMAPE value, the best hierarchical forecasting for level 0 is the bottom up approach with the smallest value, namely 30.18. Meanwhile, for level 1 with the oil and gas sector variable, it is a top down approach based on forecast proportions with the smallest value, namely 14.119, and for the non-oil and gas sector variable, it is a bottom up approach with the smallest value, namely 31.66. The research results show that for March 2023 the export value for the oil and gas sector was 1155.93 USD and for the non-oil and gas sector it was 16349.71 USD. Keywords: Export value in Indonesia, Hierarchical Forecasting, transfer function Abstrak. Peramalan hirarki adalah perincian peramalan yang memungkinkan peramalann bersama di semua tingkat hirarki. Ada dua pendekatan yang digunakan, yaitu pendekatan top-down dan bottom-up. Penelitian ini menggunakan pendekatan bottom-up, top-down proporsi historis, dan top-down proporsi peramalan. Peramalan hirarki dapat diterapkan ke beberapa model deret waktu. Model fungsi transfer digunakan dalam penelitian ini. Penelitian ini bertujuan untuk memodelkan nilai ekspor di Indonesia dengan fungsi transfer serta nilai ekspor berdasarkan disagregasi sektor ekspor. Data terbagi menjadi dua level, yaitu level 0 untuk data nilai ekspor seluruh sektor di Indonesia, serta level 1 untuk data nilai ekspor per sektor (migas dan non-migas). Berdasarkan nilai sMAPE, peramalan hirarki terbaik untuk level 0 adalah pendekatan bottom up dengan nilai terkecil yaitu 30.18. sedangkan untuk level 1 dengan variabel sektor Migas adalah pendekatan top down berdasarkan proprosi ramalan dengan nilai terkecil yaitu 14.119 dan untuk variabel sektor non Migas adalah pendekatan bottom up dengan nilai terkecil yaitu 31.66. Hasil penelitian menunjukan bahwa untuk bulan Maret 2023 nilai ekspor untuk sektor migas sebesar 1155.93 USD dan untuk sektor non migas sebesar 16349.71 USD. Kata Kunci : Nilai ekspor di Indonesia, Peramalan Hirarki, fungsi transfer